(untitled) (Altre Modernità, 2025)
This study aims to map and classify tourism promotional material collected for the DIETALY research project. The collected texts were used to build a corpus of institutional tourist publications in English aimed at promoting Italy abroad during the period 1919-1959. In the first section, the collected sources are categorised according to a genre-based based on Calvi’s model. A section focusing on multimodal linguistic analysis on some samples of brochures from the corpus will then follow. This analysis will allow for a qualitative evaluation of the communicative effectiveness of the brochures, encompassing both verbal and visual components. To achieve this, the present study considered both stylistic and structural features typical of brochures, as well as lexical, syntactic, and semantic characteristics. By comparing pre-war and post-war brochures, the paper reveals, albeit partially, how tourism communication in Italy evolved between 1919-1959. Specifically, it investigates how the language used in brochures was adapted to promote Italy to international, English-speaking visitors during this period.